Seawater carbonate chemistry and calcification mechanisms of three Hawaiian coral species (Montipora capitata, Porites compressa, Porites lobata) - Schoepf, Verena; Grottoli, Andréa G; McLachlan, Rowan H; Price, James T; Jury, Christopher P; Toonen, Robert J; De Carlo, Eric Heinen; McCulloch, Malcolm T (PANGAEA, 2025)
Here, we used boron-based geochemical proxies (δ11B, B/Ca) to investigate how three common Hawaiian coral species (Montipora capitata, Porites compressa, Porites lobata) regulate the carbonate chemistry of the calcifying fluid along a natural environmental mosaic of seawater carbonate chemistry and significant wave height. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-08-18.
Keywords: Acid-base regulation; Animalia; Benthic animals; Benthos; Cnidaria; Coast and continental shelf; Field observation; Montipora capitata; North Pacific; Porites compressa; Porites lobata; Single species; Tropical